POTENSI PASAR TRADISIONAL UNTUK MENINGKATKAN PENDAPATAN PEDAGANG - Patrisia Savera Bu’u; Tomycho Olviana; Marten R Pellokila (Universitas Nusa Cendana, 2023)
The purpose of this study is to determine the increase and the decrease in the income of traders in the Noemuti Traditional Market. Data collection was carried out using an interactive model analysis survey method. The results of the study show that Noemuti Traditional Market has little possibility of increasing the income of market traders due to three factors: unstable prices, substandard facilities and infrastructure, and unorganized market organization. The amount of income every week or month fluctuated because of the uncertainty or no buyers who shopped at the Noemuti Traditional Market. Thus, the income factors that influence the income of traders in the Noemuti Traditional Market are location, environment, communication, consumers, trader characteristics, and types of merchandise. Suggestions for future researchers are to focus more on the level of income of each trader and provide solutions for traders to overcome all existing deficiencies. Keywords: Potential; Traditional Market; Trader's Income